2014
DOI: 10.4103/0971-6203.131282
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the bystander effect in MRC5 cells after acute and fractionated irradiation in vitro

Abstract: Radiation-induced bystander effect (RIBE) has been defined as radiation responses observed in nonirradiated cells. It has been the focus of investigators worldwide due to the deleterious effects it induces in nonirradiated cells. The present study was performed to investigate whether acute or fractionated irradiation will evoke a differential bystander response in MRC5 cells. A normal human cell line (MRC5), and a human lung tumor cell line (QU-DB) were exposed to 0, 1, 2, and 4Gy of single acute or fractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These studies showed that RIBE depends on radiation quality, radiation dose, and dose rate used. RIBE was also reported in response to fractionated irradiation exposure commonly used in radiotherapy, which appears to be dependent on cell type, dose/dose rate, and the interval between fractions [ 61 , 62 ].…”
Section: Intercellular Communication In Atherosclerosis Development and The Response To Ionizing Radiation Exposurementioning
confidence: 99%
“…These studies showed that RIBE depends on radiation quality, radiation dose, and dose rate used. RIBE was also reported in response to fractionated irradiation exposure commonly used in radiotherapy, which appears to be dependent on cell type, dose/dose rate, and the interval between fractions [ 61 , 62 ].…”
Section: Intercellular Communication In Atherosclerosis Development and The Response To Ionizing Radiation Exposurementioning
confidence: 99%
“…Thus bystander effect, if it appears in vivo during fractionated radiotherapy may reduce the expected sparing effect of fractionation to adjacent tissues and even increase normal tissue damage. On the other hand, no differences were observed in micronuclei induction in normal human lung fibroblasts (MRC5) treated with conditioned medium harvested from cultures of the same line or human lung tumor cell line (QU-DB) previously exposed to 1, 2, and 4 Gy of single acute or fractionated irradiation by equal fractions with a gap of 6 h [40]. It seems that human normal fibroblasts are relatively weak recipients of bystander signaling, especially when conditioned medium is harvested shortly after irradiation.…”
Section: Bystander Effect Induced By Fractionated Irradiationmentioning
confidence: 99%
“…Another study did not show any differences in the frequency of micronucleus between a single acute dose and the fractionated one [23]. It is proposed that the effect of fractionation on the bystander effect response hinges on the radiation dose and seems to be obvious in higher doses [24].…”
Section: Introductionmentioning
confidence: 99%